Analysis of Decentralization and Local Development in Nigeria - Mukoro, Akpomuvire; Afonughe, Irikefe Omamuyovwi (PT. Riset Press International, 2025)
Nigeria became administratively divided into many constituent groups, including 774 Local Governments, multiple Local Council Development Areas, 36 states, and a Federal Capital Territory. These were intended to accelerate advancement by reacting to citizen needs, pushing governance nearer to the citizens and citizens nearer to the government to more effectively meet their demands and improve the nation's overall growth. Despite the nation's institutional decentralization, with abundant human and environmental assets readily accessible to growth, the country has significant economic hurdles. This study investigates the relationship between administrative decentralization and development in Nigeria. The study gathered data from secondary sources and researchers' observations of Nigerian government operations. The study indicated that administrative decentralization of functions reduced levels of governance without equivalent funds to carry such jobs and low tax-raising capacities by subunits of government. Some of the explanations for ineffective administrative decentralization in Nigeria include the central government's lack of political will to devolve power to subunits of government properly, the issue of resource control, corruption among decentralized area officials, conflict over the location of administrative headquarters, and failure to integrate diverse groups of decentralized areas. The study concludes that administrative decentralization has not resulted in the desired progress for Nigeria. Therefore, for administrative decentralization to promote development in Nigeria, genuine human engagement must address all of the stated difficulties.